Problem based learning: Students’ mental models on water conductivity concept - John Rafafy Batlolona; Haryo Franky Souisa (International Journal of Evaluation and Research in Education (IJERE), 2020)
This paper tells about the mental model of prospective scholars on the topic of temperature and heat. The purpose of this research is to improve students’ mental model by using problem based learning (PBL) model. The number of samples in the study amounted to 72 students with two different classes. The results of the study showed that, (1) the improvement of mental model that studied with PBL was higher than that studied with conventional learning. (2) high-skilled student mental models that are learning with PBL are higher than those studied by conventional learning. (3) low-skilled student mental models that study with PBL are higher than students learning with conventional learning. The conclusion of this study is the improvement of students' mental models using PBL models on the topic of conductivity in water. Thus the PBL model can be recommended in improving students' mental models on temperature and heat topics. The implication in this research is to improve the students' mental model as the agent of science education change.